Crowdfunding as entrepreneurial funding for investigative journalism in Portugal - Jesus-Silva, N.; Dos-Santos, M.; Baptista, N.; Mata, F. (Proceedings of the 19th European Conference on Management Leadership and Governance (ECMLG 2023), 2023)
The 2007 financial and economic subprime crisis arising from the collapse of the Lehman Brothers Bank in the USA had severe impacts on all the economic sectors. Journalism in Portugal was highly affected, and the most remarkable impacts led to editorial budget cuts. These cuts led to a drastic decrease in human resources in newsrooms, leading to a consequent breach of investigative journalism. These aspects resulted in a surge in unemployment for many experienced journalists, a decrease in the quality of information, and the consequent impoverishment and reduction of research journalism, with losses for the entire Portuguese society. Considering this context there is the need to explore alternative sources of funding for research journalism. Crowdfunding has been portrayed as an alternative to traditional models of financing research journalism, capable of generating a new dynamic, to provide for a more skilled and informed society. The main goal of this paper is to analyze crowdfunding as a tool to fund Portuguese investigative journalism. The methods include a narrative literature review on the causes, impacts, and consequences of the decrease in Portuguese investigative journalism and a case study methodology focused on the Portuguese platform of journalism crowdfunding ‘I Fund News’. In addition, qualitative research was applied to analyze the curricula of Portuguese journalism degrees with minors in entrepreneurship, business, and economics. The results show that the number of ECTS courses in entrepreneurship, business, and economics in journalism and communication degrees is very low in the Portuguese higher education sector. A relationship between entrepreneurship, business, economics, and the capacity for journalists to readapt and find the necessary funding sources is established. These results may be of interest to Portuguese police makers and higher education stakeholders, to promote the development of study programs with increased entrepreneurship, business, and economics courses. More literate journalists in the referred subjects may enhance their entrepreneurial potential and, consequently, their freelance potential to develop investigative journalism projects.